Rational Expectations of Inflation and Augmented Philips Curve Hypothesis in Sub-saharan Africa: Evidence from Dynamic Panel Data Model - (:unkn) unknown (My University, 2024)
The study focuses on how rational expectations influence augmented Philips curve hypothesis in sub-Saharan African countries using dynamic robust instrumental variable system Generalized Method of Moments (GMM) approach, with panel data from twenty-six countries in the region for the period 2009 to 2016. The two stage system GMM results show that with rational expectations on augmented Philips curve, the relationship between inflation and unemployment is positive and significant. When output gap is used as a proxy for unemployment in the model, the results reveal that the relationship between inflation and unemployment is negative but statistically insignificant. The findings suggest that the rational expectations of inflation on augmented Philips curve hypothesis are invalid in Sub-Sahara African countries. This lead to the recommendation that proper policy for the provision of enabling environment for ease of doing business to enhance productivity should be vigorously pursued in order to reduce inflation and unemployment rate.
Keywords: African Research